Prediction of Carcinogenic, Mutagenic, Hepatotoxic, and LD50 Toxicity of Herbs Euphorbia hirta and Camellia sinensis Leaf Compounds as In Silico Antihypertensive Agents - Setiani, Lusi Agus; Sari, Bina Lohita; Muntaza, Windry (Postgraduate, University of Mataram, 2023)
Hypertension is defined as an increase in systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. Treatment for hypertension is lifelong, and continuous use of conventional medications can lead to the accumulation of drugs, potentially cautilizing adverse effects on the body compared to traditional treatments. The herbal tea formulation of Euphorbia hirta herbs and Camellia sinensis leaves can lower blood pressure due to their high antioxidant activity, which is associated with hypertension-related diseases, including compounds like quercetin and myricetin. This research serves as an initial screening to assess safety and minimize side effects of the active compounds in E. hirta and C. sinensis, which are beneficial as antihypertensive agents, through in silico analysis. Toxicity predictions utilizing the ProTox II, pkCSM, and Vega-QSAR platforms, which have been verified to meet the acceptability criteria of Cooper statistics parameters, were conducted. The toxicity assessment parameters include carcinogenicity, mutagenicity, hepatotoxicity, and acute toxicity (LD50). The research results indicate that 9 compounds are carcinogenic and mutagenic, while 2 compounds are hepatotoxic. Based on the toxicity prediction assessment (LD50), it was found that quercetin and myricetin, with moderate toxicity, have LD50 values of 159 mg/kgBW